STRENGTH AND METHODOLOGY FOR ITS DEVELOPMENT - Nurimov Zafar Rakhmanberdievich (PEDAGOGS, 2024)
Annotation: “Strength”, a physical quality, is understood as the ability of a wrestler to overcome opponent resistance or resist it at the expense of muscle tension.